2016
DOI: 10.1038/nature16954
|View full text |Cite
|
Sign up to set email alerts
|

A thalamic input to the nucleus accumbens mediates opiate dependence

Abstract: Chronic opiate use induces opiate dependence, which is characterized by extremely unpleasant physical and emotional feelings after drug use is terminated. Both rewarding effects of drug and the desire to avoid withdrawal symptoms motivate continued drug use1-3, and the nucleus accumbens (NAc) is important for orchestrating both processes4,5. While multiple inputs to the NAc regulate reward6-9, little is known about the NAc circuitry underlying withdrawal. Here we identify the paraventricular nucleus of the tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

28
359
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 331 publications
(391 citation statements)
references
References 36 publications
28
359
4
Order By: Relevance
“…Optogenetic-mediated, pathway-specific stimulation reveals that the activation of inputs from the PFC, vHipp, and BLA to the NAc is rewarding and can reinforce instrumental behavior [6,7]. However, still unknown is the specific NAc circuitry that underlies negative emotional and motivational states after withdrawal.Using retrograde neuronal tracing, Zhu et al [8] showed that the NAc is densely innervated by the PVT, in addition to its well-characterized inputs from the PFC, vHipp, and BLA. Brief light stimulation of fibers that project from the PVT to the NAc evoked robust a-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPAR)-mediated excitatory postsynaptic currents in medium spiny neurons (MSNs), indicating that the PVT is a source of glutamatergic afferents to the NAc.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Optogenetic-mediated, pathway-specific stimulation reveals that the activation of inputs from the PFC, vHipp, and BLA to the NAc is rewarding and can reinforce instrumental behavior [6,7]. However, still unknown is the specific NAc circuitry that underlies negative emotional and motivational states after withdrawal.Using retrograde neuronal tracing, Zhu et al [8] showed that the NAc is densely innervated by the PVT, in addition to its well-characterized inputs from the PFC, vHipp, and BLA. Brief light stimulation of fibers that project from the PVT to the NAc evoked robust a-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPAR)-mediated excitatory postsynaptic currents in medium spiny neurons (MSNs), indicating that the PVT is a source of glutamatergic afferents to the NAc.…”
mentioning
confidence: 99%
“…Using retrograde neuronal tracing, Zhu et al [8] showed that the NAc is densely innervated by the PVT, in addition to its well-characterized inputs from the PFC, vHipp, and BLA. Brief light stimulation of fibers that project from the PVT to the NAc evoked robust a-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPAR)-mediated excitatory postsynaptic currents in medium spiny neurons (MSNs), indicating that the PVT is a source of glutamatergic afferents to the NAc.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, the NAc is also involved in the aversive emotional state linked to drug withdrawal, which induces continued and compulsive drug use. Inputs from the prefrontal cortex, ventral hippocampus, and basolateral amygdala to the NAc have been implicated in the rewarding effects of addictive drugs, while input from the paraventricular nucleus of the thalamus to the NAc mediates the physical changes and aversive memory induced by opiate withdrawal [2,3]. In addition, Wang et al [4] showed that both intraperitoneal injection of the D1 receptor antagonist, SCH23390, and intra-NAc injection of the MEK inhibitor, U0126, attenuate the propofol self-administration and diminish the expression of phosphorylated extracellular signal-regulated kinase (ERK) in the NAc.…”
mentioning
confidence: 99%